Special Features Of The Mahalla System In Uzbekistan - Ikram Mukhtarovich Matkarimov (Euro Asian Journal Publishing, 2024)
The article analyzes the general and specific aspects of the mahalla, aspects of the right of citizens of the Republic of Uzbekistan to self-government, the role of the mahallas in the development of people's spirituality
Keywords: Mahalla; state; society